2023
DOI: 10.1111/1753-0407.13384
|View full text |Cite
|
Sign up to set email alerts
|

The use of nomogram for detecting mild cognitive impairment in patients with type 2 diabetes mellitus

Abstract: Background Type 2 diabetes mellitus (T2DM) is highly prevalent worldwide and may lead to a higher rate of cognitive dysfunction. This study aimed to develop and validate a nomogram‐based model to detect mild cognitive impairment (MCI) in T2DM patients. Methods Inpatients with T2DM in the endocrinology department of Xiangya Hospital were consecutively enrolled between March and December 2021. Well‐qualified investigators conducted face‐to‐face interviews with participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“… 11 And the other proposed a nomogram based on age, marital status, per capita monthly household income, diabetes duration, diabetic retinopathy, anxiety, and depression, which showed an optimal diagnosis of MCI (C-index 0.83). 12 Similar to the above models, the risk score in this study was also developed using easily available clinical predictors and presented similar predictive ability. Although both nomogram and risk scoring tables can present the prediction model in an intuitive way, the application of risk scoring tables are more convenient for medical staff in busy clinical practice, such as the well-known Framingham risk score.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“… 11 And the other proposed a nomogram based on age, marital status, per capita monthly household income, diabetes duration, diabetic retinopathy, anxiety, and depression, which showed an optimal diagnosis of MCI (C-index 0.83). 12 Similar to the above models, the risk score in this study was also developed using easily available clinical predictors and presented similar predictive ability. Although both nomogram and risk scoring tables can present the prediction model in an intuitive way, the application of risk scoring tables are more convenient for medical staff in busy clinical practice, such as the well-known Framingham risk score.…”
Section: Discussionmentioning
confidence: 98%
“…However, previous studies mainly focused on risk factors or biomarkers associated with MCI in patients with diabetes, and few multivariate risk prediction models for MCI have been developed in T2DM patients. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
“…Our study utilized the MoCA to assess cognitive function and found that the prevalence of mild VCI was higher (58.7%) than that of MCI in T2DM patients. 32 , 33 One reason for this change might be that the MoCA was more sensitive to the diagnosis of MCI than the mini-mental state examination (MMSE). 34 …”
Section: Discussionmentioning
confidence: 99%
“…Second, total CSVD burden score, an important predictor of T2DM-related cognitive impairment, was taken into account in our study, whereas others do not. 33 , 43 , 44 Third, the online dynamic nomogram that we constructed is more convenient and intuitive for clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical decision curve analysis (DCA) will be used to measure the clinical applicability of the prediction model with ‘rmda’ R package. 59 …”
Section: Statistical Analysis Methodsmentioning
confidence: 99%